Distribution, ecology and behavior of cephalophacus bancanus borneanus horsfield in secondary and rehabilitated forests in a public university in Malaysia - Muhd Sahimi, Hani Nabilia (2017)
Cephalophacus bancanus borneanus (previously known as Tarsius bancanus borneanus) was first acknowledged by Elliot in 1990. This sub-species can be found in the Borneo Island which consists of Sabah and Sarawak of Malaysia, Brunei Darussalam and Kalimantan, Indonesia. The present study was conducted in secondary and rehabilitated forests of Universiti Putra Malaysia Bintulu Sarawak Campus (UPMKB), from October 2014 until March 2015. Through observations and captureeffort sampling covering an area of 0.37 km² secondary forest patches and 0.0713 km² of rehabilitated forest, a total of 16 tarsiers were captured using mist nets, four tarsiers were spotted through observation and a tarsier were recaptured. The population density of tarsiers captured using mist-nets in the secondary forest was 38 individuals/km² while 28 individuals/km² was recorded for the rehabilitated forest. As for distance sampling, the population density estimation was quite low thus it cannot be calculated. Morphological measurement were taken and described from the captured tarsiers. Morisita’s Index for the tarsier in secondary forest was Id = 2.42 (N = 18 tarsiers, n = 37 plots) and rehabilitated forest was Id = 7.00 (N = 2 tarsiers, n = 7 plots). Instant behavior of tarsier were described using ad libitum sampling method. Neu Habitat Preference index for secondary forest was w = 1.022 while in rehabilitated forest w = 0.884. The tree species composition and importance value index has been calculated in both plots of secondary and rehabilitated forests. Linear correlation has occur between the number of tarsier captured/ observed and the temperature in secondary forest which the value was greater than the other climatic factors correlation. The present results provided data on the presence of tarsier in both the secondary and rehabilitated forest mainly in UPMKB campus thus highlighting the conservation value of the forested areas. The data also valuable due to the status of species which is Data Deficient in IUCN redlist; and could helped the future management managing the habitat to avoid extinction.